(untitled) (AmeriQuests, 2014)
In 1954, French critic René Étiemble controversially put forward a ground-breaking thesis that exposed a hitherto unrecognised threat to the integrity and rigour of Rimbaud scholarship: namely, that objective evaluation of his poetry was becoming increasingly impeded by the profusion of highly subjective powerful myths about his short, but eventful life. This article has three aims: first, to retrace the origins and lingering impact of the most dominant myths surrounding Arthur Rimbaud –specifically the contrasting myths of the ‘Catholic convert’ and the ‘rebel artist’; secondly, through a comparative analysis of the works on Rimbaud published by Jack Kerouac and Stéphane Mallarmé, to explore the extent to which the Beat author and the Symbolist poet respectively colluded with, or questioned these myths; thirdly, to conclude that Mallarmé’s text emerges as the more balanced and convincing of the two: first, because contrary to Kerouac’s excessive self-identification with Rimbaud, especially through the seductive myth of the rebel artist, it adopts a critical distance that amply fulfils Étiemble’s timely call for a ‘de-mythologised’ approach to this poet as the prerequisite for any accurate assessment of his poetry; secondly, and more broadly, because by portraying Rimbaud as a poet whose literary reputation owes as much to the preconceptions and agendas of outside influences beyond his control than to his intrinsic artistic merits, Mallarmé’s text is equally prescient in its identification of the pitfalls of our modern-day celebrity culture.